KEPENTINGAN NASIONAL SEBAGAI DASAR ABSTENSI BELANDA TERHADAP PELANGGARAN HAK ASASI MANUSIA OLEH INDONESIA DALAM VONIS PENISTAAN AGAMA AHOK - Muhammad, Ajie Mahar; Susiatiningsih, Hermini (Journal of International Relations, 2018)
Discourses on transnational advocacies are mostly dominated by researches about the rolesof non-governmental organizations (NGO). This article aims to provide scientificdiscourse about state’s role in the practice of transnational advocacies. This studyscrutinizes Dutch abstention toward Indonesia’s human right violation in the case ofAhok’s blasphemy. This is an explanative research utilizing qualitative method whichanalyzes textual data. As conceptual frameworks, this study utilizes logic of consequences,rational choice theory and the concept of national interest to understand the DutchAbstention. This study argues that the Dutch abstention on Indonesia’s human rightviolation is the optimal choice for the sake of the continuity of Dutch interest towardIndonesia which relies on Indonesia’s strategic trust to the Netherlands. In the end, thisstudy concludes that